1993
DOI: 10.1515/cclm.1993.31.11.753
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Metamizol (Dipyrone) on the Determination of Creatinine with the Kodak Dry Chemistry Slide Comparison with the Enzymatic Method from Boehringer

Abstract: Summary:In order to eliminate positive interferences that take place with the Jaffe technique, the Kodak Ektachem and Boehringer Mannheim Companies have chosen an enzymatic method for the determination of creatinine in serum and urine. Pathological and clinical samples often contain metabolites in elevated concentrations or exogenous compounds such as drugs or toxic compounds. We noticed that patients receiving metamizol-containing drugs showed unusually low values of creatinine when determined with an Ektache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These results suggest a negative interference by metamizole, corroborating other studies performed in vitro that have demonstrated that samples containing metamizole or its metabolites present with lower values for creatinine when determined enzymatically. 19 , 20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest a negative interference by metamizole, corroborating other studies performed in vitro that have demonstrated that samples containing metamizole or its metabolites present with lower values for creatinine when determined enzymatically. 19 , 20…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of the metamizole interference in the determination of other analysis by the same principle, being purposed an interaction in the peroxidase reaction. 19 Gascon-Roche and collaborators described a significant positive interference in the determination of free triiodothyronine (T3), cortisol, estradiol and a negative interference in the carcinoembryonic antigen, human chorionic gonadotropin and α-fetoprotein, when determined by an immunoenzymatic assay based in the luminescence that uses peroxidase as a marker. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Bagnoud & Reymond(11) reported that patients receiving metamizol (Novalgin®, Litalgin®) 1 ), a widely used analgesic, had surprisingly low creatinine values, when measured with the dry slide enzymatic method of Kodak Ektachem (presently Vitros, Johnson & Johnson Clinical Diagnostics, Rochester, NY, USA). They showed clearly that methyl-amino-antipyrine, an active metabolite of the metamizol, interferes with the enzymatic tests of…”
mentioning
confidence: 99%